THE GENERAL ELECTION SUPERVISORY BODY'S STRATEGY IN PREVENTING VIOLATIONS IN THE 2024 ELECTION IN BANDUNG DISTRICT, WEST JAVA PROVINCE - Islaam, Muhammad Zakii Izzul (Jurnal Politik Pemerintahan Dharma Praja, 2024)
Bawaslu Bandung Regency always updates and improves strategies that are different from previous elections so that cases of election violations can be minimized. However, the strategy made and pursued by Bawaslu Bandung Regency for the 2024 Election has still not been able to suppress violations that have occurred, even the strategy for the 2024 Election shows that the number of violations is getting higher than the 2019 election. To find out and analyze the strategies carried out by Bawaslu in preventing violations in the 2024 elections in Bandung Regency. This research uses a qualitative method, then the technical sample used is purposive sampling and snowball sampling. The strategy of the Election Supervisory Agency (Bawaslu) of Bandung Regency in preventing violations in the 2024 Election has involved a participatory approach by involving all stakeholders. This strategy aims to increase integrity and honesty in the electoral process and ensure elections that are free from violations through effective supervision. The main supporting factor in Bawaslu's strategy is collaboration with various community organizations, educational institutions, and local governments. This collaboration allows Bawaslu to expand its network of election monitoring and education to the community, especially vulnerable groups who are prone to being targeted by money politics. However, Bawaslu also faces obstacles such as budget constraints and less than optimal community participation. To overcome these obstacles, Bawaslu needs to continue to increase collaboration and strengthen networks with various external institutions, including legal institutions and community organizations. The Bandung Regency Bawaslu's strategy in preventing violations in the 2024 elections involves a combination of participatory approaches and cross-sectoral cooperation. The success of this strategy depends on Bawaslu's ability to adapt to the macro and micro environment, utilize existing resources, and overcome various obstacles that hinder the election supervision process.